ROLE OF COMMUNICATION SKILLS OF TEACHERS AND STUDENTS IN THE TEACHING AND LEARNING PROCESS AT SECONDARY LEVEL IN TEHSIL GOJRA - Shahnila Tubbsam; Umar Farooq; Asma Hassan; Muhammad Zahir; Ayesha kalsoom (International Journal of Contemporary Issues in Social Sciences, 2024)
Effective communication skills are undeniably vital in shaping the teaching and learning process. At the heart of education lies the exchange of knowledge, ideas, and understanding between educators and students. In the context of teaching, communication skills empower educators to deliver lessons in a manner that resonates with their students. The population of this study consisted of 306 secondary school teachers (SSTs) from 62 public schools in Tehsil Gojra. The sample size was determined as 120 SSTs from 12 public schools, using convenience sampling, with a confidence level of 95% and a confidence interval of 7%. The research tool utilized in this study is a Likert scale based questionnaire. The questionnaire's reliability estimated a value of 0.754, indicating satisfactory reliability. More than half (55.8%) of the total sample was teachers from rural areas. Half (50%) of the respondents were MA or MSc degree holders. Majority (60%) of the sample was B.Ed. degree holders. Teachers with 11–15 years of experience were less than half (40%) of the sample. Majority of the respondents agree that formative assessment helps students to improve their writing skills with (M=3.97). Students’ academic achievement mostly depend on the proficiency level of speaking skills of students with (M=4.06). The major problem faced by teachers was lack of students’ interest and confidence’’ with (M=4.02). Most of the respondents agreed that learners find it difficult to ask questions because of shyness with (M=4.05). Students’ listening skills help the students take notes in the class was major strong area of students with (M=4.05). Major weak area of teachers was the difficulty to differentiate students with varying levels of learning abilities with (M=3.14). Most of the respondents agreed that teachers’ strong area was to create listening activities that are engaging and meaningful for students with (M=4.10). It was recommended that positive feedback from colleagues improves teachers’ body language with (M=4.04). Majority of the respondents agreed that class test increases students' writing skills with (M=4.07). Apart from these major recommendations teachers’ attention to solve students’ problems, teachers’ team work and training sessions, students’ presentation and group discussions improve communication skills in teaching and learning process.